Estudio de prefactibilidad para la instalación de un taller automotriz especializado en mantenimiento de llantas y neumáticos para vehículos ligeros - Contreras Samame, Alvaro Humberto (2023)
This project consists of the pre-feasibility study for the installation of an automotive workshop specialized in the maintenance of wheels and tires for light vehicles. The income that the project will obtain will be from tire maintenance services, which will be grouped under the characteristics of said services that customers need, according to the initial diagnoses that are made when entering our facilities, whether they are the general, or those that may include repair or replacement of wheels. Based on the calculated demand, it is estimated that the necessary investment to be made will be S /. 1 549 714.66, which will allow the construction of our service infrastructure, machinery, other tangible and intangible elements. Regarding the analysis carried out to the investigation, we will have many valuable points to take into account such as the sale of assets at the closing of the project. Likewise, being a specialized company, since we will be dedicated to the maintenance of tires for the automotive sector, the client will perceive and validate that our work is more dedicated, optimized, fast and efficient. Finally, and in accordance with the above and throughout this document, it will be determined that the project is technically, economically, financially and socially viable, which allows validating the proposed hypothesis. The economic results, for example, reflect a NPV of S/ 968 774 an IRR of 18% and a benefit-cost ratio of 1.29, while the financial results show a NPV of S/ 829 702, an IRR of 21% and a B / C ratio of 1.35.